“Você é aquilo que você come”: o veganismo enquanto estilo de vida e ativismo político - Londero, Debora Santos (2019)
This dissertation seeks to address the issue of veganism as a topic of research while a proposal as theme of research the veganism as a proposal of political engagement, close to matters as lifestyle and consume. In this way, I try to answer this question: Against the culture of the exploration of the animals based on a species hierarchy, how the veganism, as a “new social movement”, think their food relationship. In addition, how their abolitionist discourse contribute to open a new field of political action formed by individual and collective social engagement of his social actors? The present research try to build convergence points of the veganism as a lifestyle based in practices of ethic consume, and as movement which put itself beyond of a food regimen, but as a movement that found actions and choices from ethics. The methodology was the qualitative data analysis. The data collected by survey with open answers, with Google Forms technology, from groups of veganism in social media Facebook. Moreover the survey, was made research in loco in editions of vegan markets in the city of Santa Maria, Rio Grande do Sul. Through the years of 2017 and 2018 was made observation regularly, exploratory nonsystematized in groups from social media, especially Facebook. As a conclusion, it can be seen in veganism from two perspectives that intersect and intertwine, and that make it possible to understand it more fully. The first is to perceive veganism as a way of life, and the second is veganism as a movement, an activism, a social engagement.